Gaetano Scherillo (1905-1970): The Role of Roman Law Between Antiquity and Modern Law: Peer-reviewed article (Italian Review of Legal History, 2022)
Gaetano Scherillo was a scholar of Roman law, but also an connoisseur of modern law. His method of research and teaching, as it appears his whole scientific and didactic production, was affected by this double inclination. In view of the Centenary of the Statale, the essay analyzes the numerous courses that he wrote for students (things, succession, trial, obligations, will): in them it is possible to identify the testimony of a use of Roman law not only as a historical matter, but also – and, sometimes, above all – as an instrument for a better understanding of the present. We then focus on the role of the scholar as a precursor of the debate, still alive today, on the contents and function of Roman law as the root of European legal systems.A) On the didactic courses the following can be observed.Le cose (1945). The meaning of ‘thing’ is what is such for the social consciousness of a given age so that the notion of it becomes fluid and in can include or exclude an entity regardless of the objectivity of its physical, or chemical composition or of its philosophical representation. Among the general issues addressed in the volume, the concept of ‘patrimony’ deserves specific attention and, already from the first pages, is identified that of thing. Overall, the course is conducted with a strong exegetical sensibility and with a traditional method for reading the sources: however, a more general conceptualization is also adopted. In fact, the language used by Scherillo is that of the contemporary jurist: he analyzes the phenomena and frames them in clear and ‘geometric’ mental schemes, which are used to synthesize the complexity of historical and jurisprudential developments.La successione (1954; re-edition of Gnoli, 1997). in this volume the common thread is that of the distinction between succession in the strict sense and the mechanism of extinction and liquidation of legal relationships. As already mentioned, it is certainly Scherillo’s most significant contribution to the studies on the subject of succession, as well as the framework within which he inscribes the whole examination of the subject.The Trial (1969). The analysis is intended to be included in a more complete manual of private law: it is therefore striking that it devotes ample space to the analysis of the criminal trial. Also in this case the description of phenomena prevails on the dogmatic approach (for instance, the iurisdictio praetoria is described starting from the modern notion of jurisdiction). In this volume Scherillo describes his particular thesis on the genesis of the per formulas trial from the agere per sponsionem. Lezioni sulle obbligazioni (1962, re-edition Gnoli, 1994). Here the structure is systematic. Examples are the description of the default with refernce to the difference between the primary an d secondary precept of a rule, the notion of negative obligations, the use of the Schuld-Haftung theory. The latter, together with the distinction between primary and secondary precepts, further contributes to the description, according to the modern approach, of some categories of obligations: natural obligations, solidary obligations, ancillary obligations (also with reference to personal guarantees). Despite this, it can still be said that in this, more than in other works, the historical sense and the mind of the jurist inclined to conceptual construction find a balanced harmonization.Il testamento (1965, then 1967 and then re-edition Gnoli, 1995). The will is analysed as a legal transaction and as a document. Scherillo reiterates, in a more concise form, what he had already exposed in the monographic course on succession; here he describes the general backbone of the ‘succession system’ and inserts the single institutes into it. The study includes also the punctual and direct reading of the sources, such as that of the will of Antonio Silvano.B) As for Scherillo’s contribution to the debate on the role of Roman law in relation with the European legal systems, the essay briefly recalls the famous opposition between Betti’s more dogmatic vision and De Francisci’s more historical one, highlighting the influence that Scherillo’s method received from both these approaches. The essay terminates with some references to the current debate on the function of Roman law as the root of European legal systems and with the mention of some authors who have been studying the issue in recent times. In 1956 Scherillo had expressed himself on the importance of Roman studies with respect to contemporary law and teaching. We can affirm that he was an attentive historian and at the same time a precursor of future methods: precisely the modernity of the ideas that he supported makes them still today a fruitful subject for reflection on the issue of the relationship between Roman law and European legal science.
Keywords: Centenary of the Statale; Scherillo; dogmatic; didactic; roots of European legal systems